(untitled) (Journal of Hama University, 2022)
The study aimed at recognizing the professors’ perspectives at Hama University towards the use of info-technology for Improving the Quality of Academic Teaching, and at recognizing the differences in these perspectives according to the variables of (faculty [scientific, applied, theoretical] and years of expertise). The researchers used the descriptive analytical approach. The research community consisted of all members of teaching board in Hama University (103). The research tools was given to all of them. However, those who responded were (53). So, the research sample was (53). The researchers used to verify the objectives and questions of the study. They used the questionnaire for the use of information technology and communication for improving academic teaching. The study had the following results: The positive responses of the sample towards the use of information technology and communication for improving academic teaching in Hama University were high. There are no statistically significant differences at the level less than (0.05) among the average grades of the sample according to the variable of faculty. The mean in theoretical faculties was (108.8) with a standard deviation (16.45), the mean in applied faculties (112.0) with a standard deviation (26.44), and T-Student was (0.435). There are statistically significant differences at level less than (0.05) among the means according to the years of expertise for the sake of those members who have years of expertise between 5 and ten years. Whereas there were not any statistically significant differences between the means of those members who have between 5 to 10 years of experience and those who have less than 5 years.